Cardiovascular Response Patterns to Sympathetic Stimulation by Central Hypovolemia - Bronzwaer, Anne-Sophie G. T.; Verbree, Jasper; Stok, Wim J.; van Buchem, Mark A.; Daemen, Mat J. A. P.; van Osch, Matthias J. P.; van Lieshout, Johannes. J. (Frontiers in Physiology, 2016)
In healthy subjects, variation in cardiovascular responses to sympathetic stimulation evoked by submaximal lower body negative pressure (LBNP) is considerable. This study addressed the question whether inter-subject variation in cardiovascular responses coincides with consistent and reproducible responses in an individual subject. In 10 healthy subjects (5 female, median age 22 years), continuous hemodynamic parameters (finger plethysmography; Nexfin, Edwards Lifesciences), and time-domain baroreflex sensitivity (BRS) were quantified during three consecutive 5-min runs of LBNP at −50 mmHg. The protocol was repeated after 1 week to establish intra-subject reproducibility. In response to LBNP, 5 subjects (3 females) showed a prominent increase in heart rate (HR; 54 ± 14%, p = 0.001) with no change in total peripheral resistance (TPR; p = 0.25) whereas the other 5 subjects (2 females) demonstrated a significant rise in TPR (7 ± 3%, p = 0.017) with a moderate increase in HR (21 ± 9%, p = 0.004). These different reflex responses coincided with differences in resting BRS (22 ± 8 vs. 11 ± 3 ms/mmHg, p = 0.049) and resting HR (57 ± 8 vs. 71 ± 12 bpm, p = 0.047) and were highly reproducible over time. In conclusion, we found distinct cardiovascular response patterns to sympathetic stimulation by LBNP in young healthy individuals. These patterns of preferential autonomic blood pressure control appeared related to resting cardiac BRS and HR and were consistent over time.